Breakdown of blood-brain barrier by virus-induced cytokine during Japanese encephalitis virus infection. - Mathur, A. (1992)
In this study we have shown, for the first time, that Japanese encephalitis virus (JEV) and a low molecular weight (10 kDa) macrophage-derived neutrophil chemotactic factor (MDF) produced following JEV infection in mice could cause an alteration in the permeability of the blood-brain barrier resulting in leakage of plasma protein bound Evans blue dye and radiolabelled erythrocytes in brain. The maximum leakage occurred at day 6 after intracerebral (i.c.) JEV infection and was sensitive to anti-JEV antisera. Further, MDF caused peak leakage of dye and radiolabelled erythrocytes at 1 h post inoculation with a decline thereafter. Complete restoration of the integrity of the blood-brain barrier occurred by the 4th hour. The extent of leakage was dose dependent and showed a direct correlation between the level of MDF, clinical sickness and virus titre in brain. Anti-MDF antisera protected the mice against the effects of MDF. These findings show that JEV-induced cytokine, MDF, alters the integrity of the blood-brain barrier and thus controls the cellular and plasma leakage into the CNS.